Investigating a Role of Strategic Sourcing and Organizaiotnal Culture on Mitigating Risk in Supply Chain. Issue 2 (31st August 2014) - Kim, Minkyun; Chai, Sangmi
Abstract : The main objective of this study is to investigate an impact of organizational culture on supply chain risk and strategic sourcing. It also examines the relationship between organizational culture and strategic sourcing. By collecting 159 survey responses from supply, executives and managers of U.S. manufacturing firms, it provides empirical evidence that organizational culture and strategic sourcing mitigate supply chain risks. Organizational culture also makes a positive impact on the implementation of strategic sourcing. This study emphasizes the importance of cultural impacts to supply executives and managers in supply chain risk management.